Hubungan antara Gaya Mengajar Guru dan Gaya Belajar Peserta Didik dengan Minat dan Hasil Belajar Biologi Peserta Didik SMA di Kota Bulukumba - Husnul Inayah Saleh; Muhammad Danial; Muh Junda (Universitas Negeri Makassar, 2017)
The purpose of this study are to know the relationship between (i) the teacher's teaching style withthe learning styles of students in senior high school in Bulukumba city, (ii) the teacher's teachingstyle with the Biology learning interests, (iii) the teacher's teaching style with the Biology learningoutcomes, (iv) learning styles with Biology learning outcomes, (v) the learning interest withBiology learning outcomes of students in senior high school of Bulukumba city. This research is expost facto with data collection using questionnaires and documentation. The result descriptivestatistical of student perception of teaching style showed that have average value is 145, in goodcategory. Most student has a visual learning styles. The average values of interest is 142, in thehigh category. And the average value of student learning outcomes is 76 in good category.Hypotesis used pearson correlation test and got value of sig. 2 tailed ≤ 0,05. So, Ho rejected andH1 accepted. The results showed that (i) teachers teaching styles has relationship with learningstyles in senior high school in Bulukumba city Academic Year 2015/2016, with the relationshipstrength in the medium category; (ii) teachers teaching style has relationship with the Biologylearning interests, with the relationship strength in the low category; (iii) teachers' teaching stylehas relationship with Biology learning outcome student, with the relationship strength in the lowcategory; (iv) learning styles of learners has relationship with biology learning outcomes studentwith the relationship strength in the low category; (v) the interest of learners has relationship withbiology learning outcomes student, with the relationship strength in the medium category.